Cadmium Free Cu2ZnSnS4 Solar Cells with 9.7% Efficiency. Issue 21 (16th April 2019) - Larsen, Jes K.; Larsson, Fredrik; Törndahl, Tobias; Saini, Nishant; Riekehr, Lars; Ren, Yi; Biswal, Adyasha; Hauschild, Dirk; Weinhardt, Lothar; Heske, Clemens; Platzer‐Björkman, Charlotte
Abstract: Cu2 ZnSnS4 (CZTS) thin‐film solar cell absorbers with different bandgaps can be produced by parameter variation during thermal treatments. Here, the effects of varied annealing time in a sulfur atmosphere and an ordering treatment of the absorber are compared. Chemical changes in the surface due to ordering are examined, and a downshift of the valence band edge is observed. With the goal to obtain different band alignments, these CZTS absorbers are combined with Zn1− x Sn x O y (ZTO) or CdS buffer layers to produce complete devices. A high open circuit voltage of 809 mV is obtained for an ordered CZTS absorber with CdS buffer layer, while a 9.7% device is obtained utilizing a Cd free ZTO buffer layer. The best performing devices are produced with a very rapid 1 min sulfurization, resulting in very small grains. Abstract : Cu2 ZnSnS4 (CZTS) absorbers with different bandgaps are produced by variation of thermal treatments. These CZTS absorbers are combined with Zn1− x Sn x O y (ZTO) or CdS buffer layers. A high open circuit voltage of 809 mV is obtained for an ordered CZTS absorber with CdS, while a 9.7% device is obtained utilizing a Cd free ZTO buffer layer.